Changhong : journey to shared services - McFarlan, F. Warren (SAGE knowledge. Cases., 2016)
Since 2012, the global economy has suffered from the European debt crisis, slowing growth in emerging economies, and the Chinese economy stabilizing. Additionally, in the home appliance industry, the Chinese government has been tapering policies which had stimulated spending, such as a policy which had allowed people to exchange their old home appliances and vehicles for new ones and another one which extended the reach of home appliances to rural regions. This shifting environment has led to massive changes in the home appliance businesses. Market leader Sichuan Changhong Electric Co., Ltd., caught in this deteriorating environment has reported declining figures. In 2011, company sales were RMB 52 billion and profits of RMB 640 million, rising 27% and 19% respectively from the previous year.